2017
DOI: 10.1007/s00520-017-3957-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral curcumin for radiation dermatitis: a URCC NCORP study of 686 breast cancer patients

Abstract: Oral curcumin did not significantly reduce radiation dermatitis severity compared to placebo. The skin rating variation and broad eligibility criteria could not account for the undetectable therapeutic effect. An objective measure for radiation dermatitis severity and further exploration for an effective treatment for radiation dermatitis is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 46 publications
1
30
0
2
Order By: Relevance
“…The absence of changes in QoL scores indicates the absence of toxicities related to curcumin intake, which has also been shown in other studies (1, 55). However, in a randomized controlled trial, curcuminoid supplementation was associated with a significant improvement in QoL compared to placebo (56).…”
Section: Discussionsupporting
confidence: 85%
“…The absence of changes in QoL scores indicates the absence of toxicities related to curcumin intake, which has also been shown in other studies (1, 55). However, in a randomized controlled trial, curcuminoid supplementation was associated with a significant improvement in QoL compared to placebo (56).…”
Section: Discussionsupporting
confidence: 85%
“…Later, Ryan et al observed the protection of oral curcumin (6 g/day) administration vs. placebo after 6 months against radiation dermatitis in BC patients (n = 30) with prescribed radiation therapy (RT) [134]. The same authors tried to confirm their previous exploratory results in an ambitious trial that enrolled 686 patients with prescribed RT [135]. Nevertheless, curcumin did not reduce radiation dermatitis severity at the end of RT compared to placebo after 6 months (30 RT sessions).…”
Section: Dietary (Poly)phenols and Clinical Studies In Breast Cancer mentioning
confidence: 99%
“…COX-2 is known to participate in uncontrolled cell proliferation and suppression of apoptosis, while inducible nitric oxide synthase (iNOS) and matrix metalloproteinase-9 (MMP-9) are involved in the formation of metastases [147,148]. Several studies, both in vitro and in vivo, demonstrated that the inhibitory action of curcumin on COX-2 expression contributes significantly to its antitumor action [72,80,126]. Curcumin was also shown to inhibit the expression of MMP-9 in orthotopically implanted pancreatic [129] and ovarian [130] tumors in mice and the production of iNOS in chronic colitis [127].…”
Section: Curcumin Regulates the Activity Of Enzymes With Roles In Inflammation And Cancermentioning
confidence: 99%
“…Some authors claim that serum levels of free curcumin show a deceivingly low bioavailability because a significant fraction of the compound occurs in plasma as glucuronide and sulfate conjugates [72,158]. In the abovementioned clinical study with patients taking 3.6 g of curcumin, serum levels of the conjugates averaged 0.016 µM for curcumin glucuronide and 0.009 for curcumin sulphate [152].…”
Section: Oral Administrationmentioning
confidence: 99%
See 1 more Smart Citation